Distribution of amphibians and reptiles in central Poland: 1980-2000 - Zieliński, Piotr; Hejduk, Janusz; Stopczyński, Michał; Markowski, Janusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2005)
Based on 3047 records from 97 recorders distribution maps were drawn for the amphibians and reptiles of central Poland (lirom 51°00’N to 52°15’N and from 18°20’E to 20°20’E). The study area was divided into 180 atlas fields based on the geographic grid. All data were gathered in 1980-2000, most of them (67%) however, in 1995-2000. 13 taxa of amphibians were found in 143 atlas fields and 6 species of reptiles were found in 121 atlas fields. The amphibians were (given with the number of atlas fields with the species found): 119 - Common frog Rana temporaria Linnaeus, 1758; 114 - Common toad Bufo bufo (Linnaeus, 1758); 97 - Moor frog Rana arvalis Nilsson, 1842; 94 - Fire-bellied toad Bomhina bombina (Linnaeus, 1761); 93 - Pool frog Rana lessonae Camerano, 1882; 87 - Tree frog Hyla arhorea (Linnaeus, 1758); 85 - Green toad Bufo viriiüs Laurenti, 1768; 72 - Smooth newt Triturus vulgaris (Linnaeus, 1758); 70 - Spadefoot Pelobales fuscus (Laurenti, 1768); 69 - Edible frog Rana kl. esculenia Linnaeus, 1758; 39 - Great crested newt Triturus cristatus (Laurenti, 1768); 30 - Marsh frog Rana ridibunda Pallas, 1771 and 28 - the Natterjack Bufo calamita Laurenti, 1768. The reptile species (given with the number o f atlas fields) were: 94 - Sand lizard Lacerta agilis Linnaeus, 1758; 72 - Slow-worm Anguis fragilis Linnaeus, 1758; 67 - Common lizard Lacerta vivipara Jacquin, 1787; 60 - Grass snake Natrix natrix (Linnaeus, 1758), 57 - Adder Vipera berus (Linnaeus, 1758) and 4 - the Smooth snake Coronella austriaca Laurenti, 1768. Six adult specimens of the European pond terrapin Emys orbicularis (Linnaeus) were also found, but breeding of this species in the area studied was not confirmed.